A comprehensive review of Huangqin (Scutellaria baicalensis Georgi) tea: chemical composition, functional properties and safety aspects - Yining Quan; Zhenpeng Li; Xiangying Meng; Panpan Li; Yanying Wang; Chunnian He; Jie Shen (Beverage Plant Research)
Huangqin tea (HQT), derived from the aerial parts of various Scutellaria species, in particular S. baicalensis Georgi, has a long history of traditional use in China. Its significance has grown in recent years due to its potential anti-aging, colon cancer chemopreventive, and cardiovascular protective properties. Huangqin tea source plants have identified over 295 chemical constituents, including flavonoids, essential oils, phenolic acids, sterols, diterpenes, polysaccharides, and amino acids. Pharmacological research has underscored the diverse beneficial effects of Huangqin tea and flavonoid extracts. These effects encompass anti-inflammatory, antiviral, anti-bacterial, antipyretic, and analgesic properties, along with neuroprotective effects and protection against cardiovascular and cerebrovascular diseases. Safety studies indicate that HQT is generally safe within recommended dosages and historical use. HQT presents multifaceted potential health benefits, though comprehensive research is necessary to ensure its effectiveness and safety in human applications.